Agos designing the Bocaue Market Agriport as the pioneer for development along the Sta. Maria River - Soriano, Juan Miguel A. (College of Architecture, University of the Philippines Diliman, 2018)
The Bocaue Market Agriport is envisionde to be a hybrid facility incorporating the agricultural aspect of the pick-your-own farm with the industrial and transport-oriented component of the port and terminal with the commercial aspect of the wet and dry market. The goal of the project is to increase activity along the Sta. Maria River and incorporating the river to the daily routine of the residents of Bocaue. It is also intended as an expansion point, wherein the Bocaue Market agriport will be the center of the redevelopment of Bocaue in terms of agriculture, tourism, commerce, and overall development.